Atkin diet : the benefits and weaknessess / Noor Shahirah Azlan and Siti Jamilah Mohamad Daud - Azlan, Noor Shahirah; Mohamad Daud, Siti Jamilah (2017)
Obesity become a crucial health problem and it can lead to a many critical disease. This number is suspected to be increased, yet, at any given time, roughly 45 percent of women and 30 percent of men in United States are trying to reduce their body weight. Steward (1995) in his study identified that there are several ways to help these people to approach their normal weight management as suggested by previous research and medical like low carbohydrate diet, low fat diet, energy deficit diet. Among from that lists, low carbohydrate diet, high protein diet, high fat diet have become popular with many high selling diet books suggested this approach. However, Atkin diet become the most preferences choice of people as their method to loss their weight. Since Atkin book are launched during 1973, it really get a high demands from people. Therefore, with all controversies regarding the diet, the key question is whether or not Atkins diet is a good losing weight diet? The purpose of the study is to give insight on benefits and weaknesses of Low Carbohydrate Diet. However, this study will only focusing on Atkins Diet as it is the most popular Low Carbohydrate Diet. Researchers using secondary data to completed this research by using previous journal and article that had been done by academician around the world. Even though many people are succeed to lossen their weight by using this Atkin diet, but they have to realize that they have to bear with the consequences as well. In this research, researchers trying to highlight the benefits of this Atkin diet and the weaknesses of it.